1996
DOI: 10.1021/jm950956y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Oxazolidinone (U-100480) with Potent Antimycobacterial Activity

Abstract: During the course of our investigations in the oxazolidinone antibacterial agent area, we have identified a subclass with especially potent in vitro activity against mycobacteria. The salient structural feature of these oxazolidinone analogues, 6 (U-100480), 7 (U-101603), and 8 (U-101244), is their appended thiomorpholine moiety. The rational design, synthesis, and evaluation of the in vitro antimycobacterial activity of these analogues is described. Potent activity against a screening strain of Mycobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(114 citation statements)
references
References 11 publications
0
112
0
2
Order By: Relevance
“…Several analogues were found to possess MICs Ͻ0.125 g/ml. This potent activity in vitro was complemented by good antitubercular activity against multiple strains of M. tuberculosis (9). Most significantly, activity comparable to that of isoniazid was observed in a mouse model of M. tuberculosis infection.…”
Section: Antimycobacterial Leads With Unknown Modes Of Actionmentioning
confidence: 82%
“…Several analogues were found to possess MICs Ͻ0.125 g/ml. This potent activity in vitro was complemented by good antitubercular activity against multiple strains of M. tuberculosis (9). Most significantly, activity comparable to that of isoniazid was observed in a mouse model of M. tuberculosis infection.…”
Section: Antimycobacterial Leads With Unknown Modes Of Actionmentioning
confidence: 82%
“…35,37 sutezolid Sutezolid is a novel oxazolidinone undergoing premarketing evaluation, which -similar to linezolid, itself a first-generation oxazolidinone -exerts bactericidal activity by inhibiting bacterial protein synthesis. 38 Sutezolid has antimycobacterial activity, and in a murine model, it was found to be more potent than linezolid against M. tuberculosis. 39 In in vitro studies, sutezolid has demonstrated better antimycobacterial activity than linezolid against isolates of MDR-TB and XDR-TB.…”
Section: Pretomanidmentioning
confidence: 99%
“…The prime encounter mode of the chemical entity is through the protein synthesis inhibition of the bacilli. Another potent compound of this class, also have come on the timeline with the research investigation effort, is AZD5847 which is highly effective in intracellular bacilli as well as extracellular cells to that of linezolid without showing antagonism effect to the anti-TB regimen dugs which indicates to the development of the moiety, which has specific protein synthesis hindrance activity as the prior mechanism for anti-TB effect [49][50][51][52][53][54][55][56][57].…”
Section: Oxazolidinedione (Figure 3d)mentioning
confidence: 99%